Attacks based on social engineering in Colombia, good practices and recommendations to avoid risk - Rincón Nuñez, Paola Maritza (2023)
The article describes the analysis carried out on social engineering attacks in Colombia; as well as a compilation of good practices and recommendations to avoid risk that may be applicable to both common users and companies. Initially a brief description of the terminology related to social engineering, regulations, legislation and concepts is made, this with the purpose to familiarize the reader; Subsequently, it is possible to identify which are the most used social engineering techniques that affect the Colombian population. Another important aspect is to mention the strategies or campaigns created by state or private entities to help mitigate the occurrence of incidents related to or caused by this type of attack. Based on this, citizens, government entities and companies must address the issue as a socioeconomic problem, which can affect everything from their family environment to their work environment, or in the case of companies, their image and reputation. On the other hand, by analyzing the reported cases it was possible to identify the techniques used by cyber criminals and in order to help mitigate the insecurity gap, a set of good practices and recommendations is obtained so that people are not affected by attacks based on social engineering, this so that organizations can later use them to raise staff awareness and as a prevention strategy.